The first billion years project: the escape fraction of ionizing photons in the epoch of reionization - Paardekooper, Jan-Pieter; Khochfar, Sadegh; Dalla Vecchia, Claudio (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. Protogalaxies forming in low-mass dark matter haloes are thought to provide the majority of ionizing photons needed to reionize the Universe, due to
Gesehen am 26.06.2020